« Such sweet thunder (4.1.117) : Le trouble dans A Midsummer Night’s Dream » - François Laroque (Revue LISA)
« Turbulentia prima, tranquillitas ultima ». By that phrase the grammarian Donatus (IVth century A.D.) explains that comedy moves from initial perturbation to final reconciliation. This does seem to correspond to the structure of A Midsummer Night’s Dream where, at the outset, love is crossed, the rivers have « overborne their continents »and the seasons have altered. The green world has been put upside down and the former paradise is now a hell for the lovers. Helena thinks she has become a laughing-stock for the other three while her sense of identity is deeply disturbed. The mechanicals’ repeated blunders and malapropisms add to the overall confusion where one feels that the organs of perception have been completely mixed up. But the initial perturbation and trouble -whether it be the muddy waters of the overflowing rivers or the frantic apprehensions and imaginings of the lovers’ ‘seething brains’— slowly works itself clear through some kind of purifying process. At the end, natural rules are reinstated and the seasonal rhythms have been set right and the three weddings are now likely to prove fruitful and prosperous. Thus this comedy of errors finally exorcizes its tragic elements for the sake of some sort of fairy tale ending…